2019
DOI: 10.1182/bloodadvances.2019000706
|View full text |Cite
|
Sign up to set email alerts
|

High-level protein production in erythroid cells derived from in vivo transduced hematopoietic stem cells

Abstract: Key Points An in vivo HSC transduction/selection allows for high-level protein expression from erythroid cells without side effects on erythropoiesis. This approach that did not require ex vivo HSC manipulation and transplantation resulted in phenotypic correction of murine hemophilia A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Finally, we will have to assess in vivo if over-expression of transgenes in erythroid precursor cells can have an effect on the HSCs niche in the bone marrow or on erythrocyte differentiation, half-life and clearance 57 . Previous experiments using LV to express different proteins from erythrocytes did not show any impact on erythropoiesis [15][16][17]58 ; however, transgene-specific effects should be carefully evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we will have to assess in vivo if over-expression of transgenes in erythroid precursor cells can have an effect on the HSCs niche in the bone marrow or on erythrocyte differentiation, half-life and clearance 57 . Previous experiments using LV to express different proteins from erythrocytes did not show any impact on erythropoiesis [15][16][17]58 ; however, transgene-specific effects should be carefully evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…It could be provided as an outpatient treatment. Its efficacy has been demonstrated in several murine disease models, including b-thalassemia and hemophilia A [151,179], and its safety is currently tested in NHPs. With more gene therapy products on the horizon (such as hemophilia), the application of in vivo HSC transduction could extrapolate genetic treatments to a larger patient population.…”
Section: Discussionmentioning
confidence: 99%
“…SB1009 appeared to be superior to the PB system that exhibited a preference for integrations in regions surrounding transcriptional start sites and within long terminal repeat elements [149]. We have demonstrated the efficacy of SB1009mediated integration into HSCs by HDAd5/35++ vectors in several disease models, including b-hemoglobinopathies, hemophilia A, and Fanconi anemia (FA) [150,151]. More studies have reported gene transfer by Ad vectors expressing other transposon systems, such as PB [152], T2TP [153], and bacteriophagederived integrase PhiC31 [154].…”
Section: Random Integration Mediated By Transposasementioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to similar immunological challenges that could impact AAV-fVIII gene therapy efficacy, in vivo delivery of LV vectors can result in high transduction efficiency of antigen-presenting cells that can reduce transduction of target hepatocytes at given doses and consequently result in downstream activation of innate and adaptive anti-viral immune responses (31). As a result, in vivo delivery of LV vectors is still in the primitive phase of development, with a focus on tactics to overcome this additional immunological challenge (32)(33)(34)(35). Thus, AAV vectors are currently the leading vector in this category of gene therapy and are rapidly progressing through clinical trials (36).…”
Section: History Of Gene Therapy For Hemophilia Amentioning
confidence: 99%